Great Electrification in Peer-to-Peer Society – A New Narrative for Sustainable Futures - Sirkka Heinonen; Joni Karjalainen (University of Turku, Finland Futures Research Centre, 2022)
Electrification in Peer-to-Peer Society – A New Narrative for Sustainable Futures is a time travel journey to a future when renewable energy, electrification, and a peer-to-peer ethos are intertwined. The use of fossil fuel resources is ending.
An emission-free vision for 2050 is illustrated through four transformational scenarios: Radical Startups, Value-Driven Techemoths, Green Do-It-Yourself Engineers, and New Consciousness. The scenarios serve as testbeds for what kind of futures we want to live in. Futures have to be explored with a long perspective, but the decisions for preferred futures have to be made today. All major sectors in society have to be transformed to stay within the limits of the Paris climate goals. This book highlights results from the Neo-Carbon Energy project, addressing all those interested in future visions, societal changes and technological advances. It can also be used as teaching material, or as inspiration for concrete steps towards the post-fossil era and a carbon-neutral circular economy – for governments, companies, and citizens.
Professor Sirkka Heinonen and project researcher Joni Karjalainen are with the Finland Futures Research Centre (FFRC) at the University of Turku.